An outbreak of Streptococcus dysgalactiae subsp equisimilis in a hospital in the south of Brazil - Torres,Rosângela Stadnick Lauth de Almeida (2007)
The beta-hemolytic group C streptococci (Lancefield's group) has been considered an emergent human pathogen, showing an important role as an opportunist agent, being responsible for nosocomial infections and outbreaks. This study is reporting the first outbreak of nosocomial infection caused by Streptococcus dysgalactiae subsp. equisimilis in Brazil. From January, 2002, to December, 2004, S. equisimilis was isolated in 67/207 (32.37%) samples from secretions of patients' infected wounds, interned at the Hospital of Sanitary Dermatology in the State of Paraná (HDSPR). The prevalence of this microorganism increased from 11/42 (26.19%) in 2002, 14/65 (21.54%) in 2003 to 42/100 (42.00%) in 2004. This increase was statistically significant (p=0.024), and this microorganism became the most frequently isolated in these patients, overtaking the rates of isolation of Pseudomonas aeruginosa. The S. equisimilis grew in pure culture, as a unique microorganism, in six samples (2.9%) out of 207. Fresh feces of 15 animals (horses and sheep) living in the proximities of the hospital were also examined and three of them positive for S. equisimilis. The biochemical profile of the strains isolated from the patients and from the animals was the same. These animals might have been the source of the dissemination of the outbreak in the hospital. New studies will be necessary to confirm the genetic relationship between the strains isolated from patients and animals.